Some Unresolved Dilemmas - Carter, Donald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
This paper deals with some of the basic problems created by the adoption of collective bargaining, procedures by faculty at Canadian colleges and universities.